POLÍTICA DE CONSUMO: MOVIMENTO SOCIAL DE DEFESA DO CONSUMIDOR NO BRASIL - Costa, Nelson Nery (2014)
The doctoral thesis, defended for the graduation in Public Policies from the Federal University of Maranhao, with the Consumation Policies: the consumers protection in Brazil social movement . The goal of the research was to study and understand the institutional influence achieved by the movement from the 1988 Constitution s dispositions as well as the 1990 Consumer s Protection Code. The main problem of the doctoral thesis was to know if whether the social movement was somehow responsible for the diffusion, claim and establishment of the consumer s rights in Brazil, at the end of the 20th century. As secondary problems, the following questionings arose: a) how the workers acquired rights to become the current consumers?; b) how the Brazilian consumer society was formed?; c) how was the consumer s protection movement expressed in Brazil?; d) what are the characteristics of the consumer s rights and the National Policy of Consumption Relations? To answer, a research following the dialectical method based on the Karl Marx and other authors who followed his general orientation, from several currents and shades concepts of capitalism, merchandise, alienation, market, capital-gain and worker. At the end of the 20th century in Brazil, the thesis was the defense of the free market and free competition, based on the principles of contractual freedom and linking force of what was legally agreed. As the antithesis was the social movement for the consumer s defense, that defended changes in the constitution regarding consumer s rights and the connected public policy. As a synthesis of this conflict, the 1988 Constitution approached the theme, and soon after, the Consumer s Protection Code itself in 1990. From the shock, constitutional provisions were created followed by its codification as a synthesis of the earlier opposites conflict, leading to a new consumer conscience supporting consumer awareness and consumption relationships policies. The secondary hypothesis were answered, confirming its assertive that: a) alienation though consumption solidified the basis of the capitalist social unit; b) slowly, a consumption society was created in Brazil based on the dependence of transnational companies; c) several consumer protection movements and public administration offices articulated and organized to create a consumption policy; d) the consumer protection policies were established based on the protection of the disadvantaged, the vetting of abusive and surprise clauses, the linkage between advertisement and product, consumer s education, nature protection, the participation of associations and use of class action suits. Finally, the main hypothesis was considered, leading to the conclusion that the consumer protection social movement was responsible for the establishment of Brazil s public consumption policies, at the end of the last century, especially with the creation of the consumer s protection in the 1988 Constitution and the establishment of the National Policy of Consumption Relations in the 1990 Consumer s Protection Code.